Modulatory Effect of Ascorbic Acid (Vitamin C) on Cyclophosphamide-Mediated Antitumor Activity and Mutagenicity in Mice Bearing Ascites Dalton's Lymphoma - S. B. PRASAD; B. M. NICOL; G. ROSANGKIMA; AMENLA (International Journal of Pharma and Bio Sciences, 2010)
Cyclophosphamide is an anticancer drug with immunosuppressive activities. Considering various reports on the possible antioxidant/protective functions of ascorbic acid, it is aimed at to explore the modulatory effect of ascorbic acid on therapeutic efficacy as well as mutagenic potentials of cyclophosphamide in the same tumor bearing mice. Swiss albino mice with ascites Dalton’s lymphoma were used for the experiments. Combination treatment of mice with ascorbic acid and cyclophosphamide showed a significant increase in life span as compared to that of cyclophosphamide alone. As compared to cyclophosphamide alone, the frequency of mutagenic parameters were lessened after combination treatment with ascorbic acid and cyclophosphamide. The glutathione level in tumor cells increased with tumor growth. The treatment of tumor-bearing mice with cyclophosphamide alone or in combination with ascorbic acid caused a decrease in protein, glutathione levels and lactate dehydrogenase (LDH) activity, and an increase in lipid peroxidation (LPO) in tumor cells.